1991
DOI: 10.1042/bj2750727
|View full text |Cite
|
Sign up to set email alerts
|

Similarity between physicochemical properties of recombinant rat prorenin and native inactive renin

Abstract: Rat prorenin was synthesized by Chinese-hamster ovary cells transfected with an expression vector containing rat preprorenin cDNA sequences, then purified by concanavalin A-Sepharose chromatography and h.p.l.c. on G3000SW. The molecular mass of purified prorenin was 46,000 Da, as determined by h.p.l.c. on G3000SW. Immunoblot analysis indicated that recombinant prorenin cross-reacted with anti-(mature renin) antibody and two kinds of antibodies recognizing the N-terminus and C-terminus of the prosegment of rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…No difference was found between the two strains of rats with respect to the molecular mass, immunoreactivity, and affinity for con A. Furthermore, all these properties of adrenal active renin are similar to those observed for active renin from the kidney 31 -33 - 35 and plasma. 31 - 33 Thus, the increase in adrenal renin activity in SHRSP may be caused by the increased amount of active renin rather than the appearance of renin isoenzyme with higher enzymatic activity.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…No difference was found between the two strains of rats with respect to the molecular mass, immunoreactivity, and affinity for con A. Furthermore, all these properties of adrenal active renin are similar to those observed for active renin from the kidney 31 -33 - 35 and plasma. 31 - 33 Thus, the increase in adrenal renin activity in SHRSP may be caused by the increased amount of active renin rather than the appearance of renin isoenzyme with higher enzymatic activity.…”
supporting
confidence: 55%
“…Inactive renin in each fraction was calculated as the difference between total and active renin. Preliminary experiments showed that the recovery of pure rat renal active renin 34 and purified recombinant rat prorenin 35 from a G3.000SW column was 91±3 (n=6) and 89±3% (n=6), respectively.…”
Section: Measurement Of Plasma Proreninmentioning
confidence: 99%
“…which contains the mouse dhfr gene was separated on an agarose gel and ligated to the NruI-BamHI fragment (1.6 kb) derived from plasmid pCDM8 (Seed, 1987) harbouring the CMV promoter and XhoI site to yield the pCVD(X) plasmid. Figure l( b) shows the structure of the plasmid pSVD(X) which resulted from transformation of the BamHI site in pSVD (Hosoi et al, 1991) to the XhoI site. A 1.3 kb EcoRI-XhoII cDNA fragment containing the entire coding sequence of Xenopus BMP-4 (Nishimatsu et al, 1992) was blunt-ended with T4 DNA polymerase and ligated with XhoI linkers.…”
mentioning
confidence: 99%